(untitled) (Journal of Economic Research & Business Administration, 2016)
In the present article the author considered the factors influencing formation of logistic costs. The following groups of the factors impacting on formation of logistic costs are marked: external and internal; positive and negative; regulated/controllable and unregulated / uncontrollable. Having studied impact of factors, performing operations to reduce the level of logistic costs is possible. Reducing the level of logistic costs could be reached by: – reductions and minimizing stocks quantity (including due to acceleration of their turnover); – rational use of transport communications (due to load and balance of vehicles and routes); – implementation of innovative technologies in productions; – improvement of management of logistic processes (that also allows to lower costs of aging and exhaustion of stocks); – use of the modern information systems increasing effective management of streams.